Eka Kurniawan’s projection of women and patriarchal society: a radical feminist study of Beauty is a wound - Salam, Saima Piash Binte (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.